METODE PELAKSANAAN FONDASI BORED PILE DAN REDESIGN FONDASI TIANG PANCANG APARTMENT MALIOBORO CITY YOGYAKARTA - , MUHAMMAD ANHAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is one of the world tourist destinations of the world where there are historical relics and beautiful natural resources. Visited One of the town is the city of Yogyakarta. For this reason, many hotels and apartments have been built in Yogyakarta. One such development is done by PT. Inti Hosmed development. PT. Inti Hosmed pioneered the development of a dwelling that can be used as a source of investment that is at once comfortable residential superblock Malioboro city. The aims of this study is to determine the foundation strength were optimal and efficient. The methodology used in this research is booring and casting methods. And on redesign piling foundation use based of material strength method and Skempton method